2023
DOI: 10.1002/smll.202204993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Resolution Nanostructure and Dynamics of the Deep Eutectic Solvent—Graphite Interface as a Function of Potential

Abstract: Interest in deep eutectic solvents (DESs), particularly for electrochemical applications, has boomed in the past decade because they are more versatile than conventional electrolyte solutions and are low cost, renewable, and non‐toxic. The molecular scale lateral nanostructures as a function of potential at the solid–liquid interface—critical design parameters for the use of DESs as electrochemical solvents—are yet to be revealed. In this work, in situ amplitude modulated atomic force microscopy complemented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The minor influence of applied surface potential on the diameters and heights of the EAN disks indicates that the near‐surface nanostructure do not change much with the applied potential, even though the Stern layer changes substantially. [ 25a,26 ] This is likely because the potential is largely neutralized by the Stern layer, or the changes in the Stern layer structure with potential have little influence on the near‐surface structures for graphite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The minor influence of applied surface potential on the diameters and heights of the EAN disks indicates that the near‐surface nanostructure do not change much with the applied potential, even though the Stern layer changes substantially. [ 25a,26 ] This is likely because the potential is largely neutralized by the Stern layer, or the changes in the Stern layer structure with potential have little influence on the near‐surface structures for graphite.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3a,17b,24 ] A few AFM studies experimentally probed the lateral structure of Stern layers of ILs, [ 25 ] and other concentrated electrolytes. [ 26 ] These studies showed that the Stern layer composition responds as expected when potential is changed, but that lateral structures can be unexpectedly complex. [ 25a,26,27 ] The lateral IL nanostructure near an electrode surface has not been studied before, and the effect of an applied potential is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation